A cross-sectional survey of Indians in Kuwait with risk factors for coronary artery disease - Purohit, Sangeeta; Purohit, Prashant (International Journal Of Community Medicine And Public Health, 2019)
Background: The Indian sub-population is the biggest among the foreigners in Kuwait. Due to the harsh weather conditions most of the time in the year there is less inclination towards a healthy lifestyle. The present study was conducted to determine the extent of the Indian population living in Kuwait having the risk factors for coronary artery disease (CAD). Methods: A cross-sectional survey was conducted including 400 subjects aged 18 years or more (346 males and 54 females). They were subjected to general physical examination, and were asked to respond to a standard questionnaire. Results: Significantly more females than males were found to be overweight (63% vs. 43.9%, p<0.01) or obese (16.7% vs. 4.3%, p<0.005). Females also had higher proportions than males in having inadequate physical activity (79.6% vs. 53.2%, p<0.001). Significantly more males were having an inadequate intake of fruits and vegetables as compared to females (34.7% vs. 18.5%, p<0.005). There was no significant difference between the genders in proportions of hypertension, smoking, and diabetes. Overweight, hypertension, and inadequate physical activity showed a rising trend with increasing age. The studied population was compared with several geographically different populations, as well as the different populations living in India. Conclusions: As the stay and the jobs of Indians in Kuwait depend upon their health-status, prevention of CAD is of paramount importance. Looking at the levels of the prevalence of several risk factors, multilevel interventions are needed for reducing the CAD-morbidity and mortality.